(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article describes technological defects that occur in the manufacture of clothing and several proposals for their elimination. In addition, the article provides information on the design calculations used in clothing design, the structure of the human body, the properties of the fabrics that make up the clothing package, and other factors.